Extensive Diversity of RNA Viruses in Australian Ticks - Harvey, Erin; Rose, Karrie; Eden, John-Sebastian; Lo, Nathan; Abeyasuriya, Thilanka; Shi, Mang; Doggett, Stephen L; Holmes, Edward C (Journal of virology, 2019)
Understanding the microbiome of ticks in Australia is of considerable interest given the ongoing debate over whether Lyme disease and its causative agent, the bacterium , are present in Australia. The diversity of bacteria infecting Australian ticks has been studied using both culture- and metagenomics-based techniques. However, little is known about the virome of Australian ticks, including whether this includes viruses with the potential to infect mammals. We used a meta-transcriptomics approach to reveal the diversity and evolution of viruses from Australian ticks collected from two locations on the central east coast of Australia, including metropolitan Sydney. From this we identified 19 novel RNA viruses belonging to 12 families, as well as 1 previously described RNA virus. The majority of these viruses were related to arthropod-associated viruses, suggesting that they do not utilize mammalian hosts. However, two novel viruses discovered in ticks feeding on bandicoot marsupials clustered closely within the mammal-associated hepacivirus and pestivirus groups (family ). Another bandicoot tick yielded a novel coltivirus (family ), a group of largely tick-associated viruses containing the known human pathogen Colorado tick fever virus and its relative, Eyach virus. Importantly, our transcriptomic data provided no evidence for the presence of in any tick sample, providing further evidence against the presence of Lyme disease in Australia. In sum, this study reveals that Australian ticks harbor a diverse virome, including some viruses that merit additional screening in the context of emerging infectious disease. Each year a growing number of individuals along the east coast of Australia experience debilitating disease following tick bites. As there is no evidence for the presence of the causative agent of Lyme disease, , in Australian ticks, the etiological basis of this disease syndrome remains controversial. To characterize the viruses associated with Australian ticks, particularly those that might be associated with mammalian infection, we performed unbiased RNA sequencing on 146 ticks collected across two locations along the coast of New South Wales, Australia. This revealed 19 novel RNA viruses from a diverse set of families. Notably, three of these viruses clustered with known mammalian viruses, including a novel coltivirus that was related to the human pathogen Colorado tick fever virus.